Strategi Pengembangan Wisata Mangrove Desa Pene Berbasis Media Sosial dan Kesiapan Destinasi - Sokor Rozi, Muhammad; Syukron, MA; Syahrul Munir, M. (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study aims to evaluate the management of mangrove forest tourism through a 4A analysis (Attraction, Accessibility, Amenities, and Ancillary Services) as well as the role of social media as a tool for promotion and education. A qualitative method was employed using interviews, observations, and document review involving key informants, namely the hamlet head and local community members.The results show that the main attractions include natural beauty, biodiversity, and attractive trekking paths. However, accessibility and supporting facilities still require improvement, particularly in terms of transportation and complementary services such as tour guides. The use of social media has not been optimal and remains sporadic, thus failing to fully maximize promotional potential. Supporting factors in tourism management include the extensive mangrove area, the presence of hills suitable for camping areas, and increasing public awareness of biodiversity through social media. Meanwhile, inhibiting factors include low community responsiveness, limited road access, and inadequate accessibility and supporting facilities from the village government. Although some community members have promoted the destination on social media, these efforts are inconsistent, and there is no dedicated management account such as on TikTok or Instagram. An important recommendation is that the village government should establish a digital management team and allocate a promotional budget, while local communities should be actively involved in content creation and tourism services. Collaboration between the two can enhance promotion through social media, improve basic infrastructure, and strengthen tourism attractions, thereby making the destination more prepared and attractive to visitors.